Highly selective optical detection in a lab-on-a-chip for biological fluids analysis - Minas, Graça (2002)
This paper presents a microfluidic system for determining the protein concentrations in human biological fluids (e.g. urine) with a highly sensitive and selective optical photodetector based on a Fabry-Perot filter. The microsystem consists of two wafers: a Pyrex glass wafer containing the microlaboratory (microchannels to carry chemical reagents and sample solutions) and a silicon wafer that includes the protein detection system and readout electronics. The optical channel operates in the visible spectral range. Optical simulations of the Fabry-Perot filter for narrow band operation are demonstrated by the determination of total protein and albumin concentration in urine. Compensation techniques for the detection system are also presented. This microfluidic system eliminates the need for expensive readout optics and opens the door to low-cost disposable devices.